Glocal culture, sporting decline? Globalization and football in Scandinavia. Issue 4 (3rd April 2019) - Andersson, Torbjörn; Hognestad, Hans
Abstract: This chapter looks at how globalization has affected and shaped the domestic elite level male football cultures of Scandinavia since the game turned more professional in the region. By drawing on empirical examples from the recent histories of Norwegian, Swedish and, to a lesser extent, Danish football, the authors analyse how the sporting cultures of these countries have changed since the 1970s. The amateur ideologies which had previously dominated football in Scandinavia faded during a period when influences from international and especially professional English football intensified. These influences stretched from playing styles to spectator cultures. While these influences initially made clubs and teams from Scandinavia more competitive in international football, the 'hypercommodification' which has dominated top level European football in the new millennium has to a large extent affected Scandinavian football in a negative way in terms of sporting competitiveness. Simultaneously the authors argue that global influences have injected significant fuel and new energy to the spectator cultures evident in a large number of Scandinavian football club communities.